1999
DOI: 10.1046/j.1432-1327.1999.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyanophycinase, a peptidase degrading the cyanobacterial reserve material multi‐L‐arginyl‐poly‐L‐aspartic acid (cyanophycin)

Abstract: The branched polypeptide multi-l-arginyl-poly-l-aspartic acid, also called cyanophycin, is a water-insoluble reserve material of cyanobacteria. The polymer is degraded by a specific hydrolytic enzyme called cyanophycinase. By heterologous expression in Escherichia coli, a gene encoding cyanophycinase has been identified in the sequenced genome of Synechocystis sp. PCC 6803. The gene, designated cphB, codes for a protein of 29.4 kDa. The high level of expression of active cyanophycinase in E. coli from the Syne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
126
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(129 citation statements)
references
References 32 publications
(58 reference statements)
3
126
0
Order By: Relevance
“…Based on the observation that cphB and cphA from Synechocystis sp. PCC 6803 can independently be expressed in E. coli when cloned in the two possible orientations, it has been suggested that the cphB-cphA gene cluster would not be cotranscribed in this cyanobacterium (12). Additionally, cyanophycin synthetase and cyanophycinase of different cyanobacteria can show different relative abundances under different physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the observation that cphB and cphA from Synechocystis sp. PCC 6803 can independently be expressed in E. coli when cloned in the two possible orientations, it has been suggested that the cphB-cphA gene cluster would not be cotranscribed in this cyanobacterium (12). Additionally, cyanophycin synthetase and cyanophycinase of different cyanobacteria can show different relative abundances under different physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…10, 12, and 37). Gene cphB1 would encode a cyanophycinase of 298 amino acids showing 99% identity to CphB from A. variabilis (12) and 60% identity in a 269-amino acid overlap to cyanophycinase from Synechocystis sp. PCC 6803 (37).…”
Section: Identification Of Two Clusters Of Cyanophycin Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding enzyme, cyanophycinase (CphB), was purified from a recombinant E. coli harboring the cphB gene from Synechocystis sp. PCC6803 and characterized in detail (8). Dipeptides consisting of arginine plus aspartic acid and free arginine were identified as products of CGP degradation in addition to small amounts of aspartic acid (8).…”
mentioning
confidence: 99%
“…PCC6803 and characterized in detail (8). Dipeptides consisting of arginine plus aspartic acid and free arginine were identified as products of CGP degradation in addition to small amounts of aspartic acid (8). In contrast to intracellular degradation, nothing is known about the extracellular decomposition of this biopolymer by bacteria or other microorganisms.…”
mentioning
confidence: 99%